Short-term effects of physical activity, air pollution and their interaction on the cardiovascular and respiratory system. (August 2018) - Laeremans, Michelle; Dons, Evi; Avila-Palencia, Ione; Carrasco-Turigas, Glòria; Orjuela, Juan Pablo; Anaya, Esther; Cole-Hunter, Tom; de Nazelle, Audrey; Nieuwenhuijsen, Mark; Standaert, Arnout; Van Poppel, Martine; De Boever, Patrick; et al.
Abstract: Physical activity (PA) in urban environments may lead to increased inhalation of air pollutants. As PA and air pollution (AP) have respectively beneficial and detrimental effects on the cardiorespiratory system, the responses to these exposures can interact. Therefore, we assessed the short-term effects of PA, AP and their interaction on a set of subclinical cardiovascular and respiratory outcomes in a panel of healthy adults: heart rate variability (HRV), retinal vessel diameters, lung function and fractional exhaled nitric oxide (FeNO). One hundred twenty two participants measured their PA level and exposure to black carbon (BC), a marker of AP exposure, with wearable sensors during an unscripted week in three different seasons. The study was part of the PASTA project in three European cities (Antwerp: 41 participants, Barcelona: 41 participants, London: 40 participants). At the end of each measurement week, the health outcomes were evaluated. Responses to PA, BC and their interaction were assessed with mixed effect regression models. Separate models were used to account for a 2-h and 24-h time window. During the 2-h time window, HRV and lung function changed statistically significantly in response to PA (METhours) and logarithmic BC (%change). Changes in HRV marked an increased sympathetic tone with both PA (logarithmic LF/HF: +7%; p < 0.01) and BC (logarithmic HF: −19%; p < 0.05). In addition, PA provoked bronchodilation which was illustrated by a significant increase in lung function (FEV1 : +15.63 mL; p < 0.05). While a BC %increase was associated with a significant lung function decrease (PEF: −0.10 mL; p < 0.05), the interaction indicated a potential protective effect of PA ( p < 0.05). We did not observe a response of the retinal vessel diameters. Most subclinical outcomes did not change in the 24-h time window (except for a few minor changes in LF/HF, FeNO and PEF). Our results on the separate and combined effects of short-term PA and AP exposure on subclinical markers of the cardiorespiratory system are relevant for public health. We provide insights on the physiological responses of multiple, complementary markers. This may move further research towards elucidating potential pathways to disease and the long-term clinical impact of the observed physiological changes. Highlights: Real-world PA and BC exposure was assessed with wearable sensors to investigate their combined effects. HRV decreased with both PA and BC, but there was no interaction effect. PA may protect against lung function decrease associated with acute BC exposure. Clarification of the longitudinal behavior of short-term changes needed to understand long-term clinical impact.